The reserve army of labour in the postwar U.S. economy: Some stock and flow estimates - Deepankar Basu (University of Massachusetts, Department of Economics, 2012)
This paper presents some estimates of the stock of the reserve army of labour, and flows into and out of the reserve army of labour for the postwar U.S. economy. Estimates of stocks are presented for the period 1948 - 2011 at a monthly frequency; 6 month moving average estimates of flows into and out of the reserve army of labour are presented for the period 1990 - 2011. Some interesting patterns in the stock and flow data are pointed out, and it is suggested that this data base on the active and reserve army of labour can be used for empirical analysis of the labour market from a Marxian theoretical perspective.
Keywords: B51; O1; 330; Marxian political economy; reserve army of labour; labour market